IMPLEMENTASI KAIDAH ḤAML AL-MUTLAQ `ALᾹ AL-MUQAYYAD DALAM KITAB TAFSIR AL-MUNĬR DAN KITAB TAFSIR AL-JĀMI` LI AḤKĀM AL-QUR’AN - Ikmal, Ikmal; Agil, Mujahid; wahyudi, Wahyudi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
His study aims to reveal the use of one of the rules of interpretation, namely the rule of ḥaml al-muṭlaq `alā al-muqayyad in the book of interpretation. In this study, the author describes three important points, namely the understanding of muṭlaq and muqayyad, the law in the rule of ḥaml al-muṭlaq `alā al-muqayyad, and the implementation of the rule of ḥaml al-muṭlaq `alā al-muqayyad in two books of interpretation, the interpretation of al-munĭr and the interpretation of al-jāmi` li aḥkām al-qur'an. This type of research is classified as library research with a descriptive comparative analytical method. Through this study, the author explains that muṭlaq is a word that indicates an unlimited entity, while muqayyad is a word that indicates a limited entity. From a legal aspect, muṭlaq and muqayyad have four laws taking into account legal conditions and causes. Wahbah al-zuḥailĭ and al-qurṭubĭ implement the concept of the kiadah ḥaml al-muṭlaq `ala al-muqaayad in their interpretations either explained explicitly or simply explaining universal legal conclusions